Exploring the potential of cold plasma treatment followed by zinc-priming for biofortification of buckwheat sprouts - Starič, Pia; Remic, Lucija; Vogel-Mikuš, Katarina; Junkar, Ita; Vavpetič, Primož; Kelemen, Mitja; Pongrac, Paula (Frontiers in Nutrition, 2023)
Increasing the concentration of an element in edible produce (i.e., biofortification) can mitigate the element deficiency in humans. Sprouts are small but popular part of healthy diets providing vitamins and essential elements throughout the year. Element composition of sprouts can easily be amended, e.g., by soaking the grains in element-rich solution before germination (grain-priming). In addition, pre-treatment of grains to improve element translocation from the solution into the grain may further enhance the element concentration in the sprout. Cold plasma technique could provide such solution, as it increases wettability and water uptake of grains. Grains of common buckwheat (Fogopyrum esculentum Moench) were pre-treated/ untreated with cold plasma and soaked in ZnCl2 solution/pure water. Germination tests, α-amylase activity, grain hydrophilic properties and water uptake were assessed. Element composition of grain tissues and of sprouts was assessed by micro-particle-induced-X-ray emission and X-ray fluorescence spectroscopy, respectively. Grain-priming increased Zn concentration in shoots of common buckwheat sprouts more than five-times, namely from 79 to 423 mg Zn kg−1 dry weight. Cold plasma treatment increased grain wettability and water uptake into the grain. However, cold plasma pre-treatment followed by grain-priming with ZnCl2 did not increase Zn concentration in different grain tissues or in the sprouts more than the priming alone, but rather decreased the Zn concentration in sprout shoots (average ± standard error: 216 ± 6.13 and 174 ± 7.57 mg Zn kg−1 dry weight, respectively). When the fresh weight portion of whole sprouts (i.e., of roots and shoots) was considered, comparable average requirements of Zn, namely 24.5 % and 35 % for adult men and women would be satisfied by consuming cold plasma pre-treated and not pre-treated grains. Potential advantages of cold plasma pre-treatment need to be tested further, mainly to optimize the duration of soaking required to produce Zn-enriched sprouts.